GIS-integrated spatial analysis models for imaging geomorphology of Mroga and Mrożyca interfluvial area (Central Poland) - Majecka, Aleksandra; Dmochowska-Dudek, Karolina (Acta Geographica Lodziensia, 2021)
GIS data processing techniques are currently being used to revise many ideas in the field of geomorphology and related scienc-es. The paper presents the characteristics of the landform relief of the Mroga and Mrożyca interfluvial area (on the northern margin zone of the Łódź Plateau) based on the results of GIS spatial analysis models. These are techniques that have not been used so far for such a detailed fragment of the Łódź Plateau. The aim of this paper was to show the possibility of detailing topographic and geomorphological analysis and re-imagining the features of the Łódź Plateau relief on the example of a case study of the Mroga and Mrożyca interfluvial area. In this case, the use of GIS modelling confirmed the main features of the strongly transformed relief of the Mroga and Mrożyca interfluvial area, which is a result of overlapping elements of relief formed during the Warta stadial of the Odra Glaciation and further, during periods of the Vistulian and Holocene morphogenesis.